2002
DOI: 10.1103/physrevb.66.144501
|View full text |Cite
|
Sign up to set email alerts
|

Spin correlations in the algebraic spin liquid: Implications for high-Tcsuperconductors

Abstract: We propose that underdoped high Tc superconductors are described by an algebraic spin liquid (ASL) at high energies, which undergoes a spin-charge recombination transition at low energies. The spin correlation in the ASL is calculated via its effective theory -a system of massless Dirac fermions coupled to a U (1) gauge field. We find that without fine tuning any parameters the gauge interaction strongly enhances the staggered spin correlation even in the presence of a large single particle pseudo-gap. This al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
239
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(256 citation statements)
references
References 52 publications
17
239
0
Order By: Relevance
“…adj : LO B (3) adj : NLO B (3) adj : N 2 LO Padé (2,1) B (3) adj : N 2 LO Padé (1,2) For B (0) adj , the prediction from large-N f is [4,6] 19) and the extrapolations obtained from the three-form and scalar adjoints give…”
Section: Bilinears As D →mentioning
confidence: 99%
See 2 more Smart Citations
“…adj : LO B (3) adj : NLO B (3) adj : N 2 LO Padé (2,1) B (3) adj : N 2 LO Padé (1,2) For B (0) adj , the prediction from large-N f is [4,6] 19) and the extrapolations obtained from the three-form and scalar adjoints give…”
Section: Bilinears As D →mentioning
confidence: 99%
“…At large N f , the gauged U(1) current, ψ i γ (3) µ ψ i , is set to zero by the EOM of the gauge field, hence the operator Q 1 is an EOM-vanishing operator. However, besides Q 3 , there still is…”
Section: Four-fermion Operators As D →mentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper we will focus on one such state that has played a central role in some previous theoretical work 24,25,26,27,28,29 on the cuprate problem. This state -dubbed the d-wave RVB or staggered flux (sF) spin liquid -is a quantum paramagnet that nevertheless has gapless spin carrying excitations.…”
Section: Introductionmentioning
confidence: 99%
“…However, with large enough fermion numbers N , the system is believed to be described by a conformal field theory (CFT), with the fixed point gauge field coupling e * 2 ∼ 1/N . Physics based on this conformal field theory at large-N case has been studied in many references 1,2,3,4 , and it has been shown that the order parameters of various spin ordered patterns with different symmetry breaking can be all described as fermion bilinears at these critical spin liquids.…”
Section: Introductionmentioning
confidence: 99%